Regulation of Polycomb Repression by O-GlcNAcylation: Linking Nutrition to Epigenetic Reprogramming in Embryonic Development and Cancer - Decourcelle, Amélie; Leprince, Dominique; Dehennaut, Vanessa (Frontiers in Endocrinology, 2019)
Epigenetic modifications are major actors of early embryogenesis and carcinogenesis and are sensitive to nutritional environment. In recent years, the nutritional sensor O-GlcNAcylation has been recognized as a key regulator of chromatin remodeling. In this review, we summarize and discuss recent clues that OGT and O-GlcNAcylation intimately regulate the functions of the Polycomb group proteins at different levels especially during Drosophila melanogaster embryonic development and also in human cancer cell lines. These observations define an additional connection between nutrition and epigenetic reprogramming associated to embryonic development and cancer.